2017
DOI: 10.3390/nu9091000
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Ethanolic Extracts from Artichoke, an Edible Herbal Medicine, against Acute Alcohol-Induced Liver Injury in Mice

Abstract: Oxidative stress and inflammation are well-documented pathological factors in alcoholic liver disease (ALD). Artichoke (Cynara scolymus L.) is a healthy food and folk medicine with anti-oxidative and anti-inflammatory properties. This study aimed to evaluate the preventive effects of ethanolic extract from artichoke against acute alcohol-induced liver injury in mice. Male Institute of Cancer Research mice were treated with an ethanolic extract of artichoke (0.4, 0.8, and 1.6 g/kg body weight) by gavage once da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 41 publications
3
77
0
1
Order By: Relevance
“…Also, administration of artichoke leaf extract (Al‐Ahdab, ; Colak et al, ) or artichoke leaves (Abdel‐Kader et al, ) in rats with hepatotoxicity induced by carbon tetrachloride (CCl4) decreased MDA and diene conjugate (DC) levels and improved antioxidant parameters (i.e., activity of SOD, GPx, GSHm and CAT) and histopathological findings of hepatocytes compared with CCL4 treated rats. The artichoke leaf extract consumption in rats with paracetamol‐induced hepatotoxicity (El Morsy & Kamel, ), and in mice with acute alcohol‐induced liver injury (Tang et al, ) showed similar results favor to protect liver from toxicity induced by paracetamol and alcohol. But, Mehmetcik et al () observed that MDA and DC levels decreased and GPx activity and GSH level increased, whereas SOD activity and levels of vitamin E and vitamin C did not change significantly in liver tissue of rats with carbon tetrachloride‐induced hepatic injury after administration of artichoke leaf extract (1.5 mg/kg) for 2 weeks.…”
Section: Resultsmentioning
confidence: 91%
“…Also, administration of artichoke leaf extract (Al‐Ahdab, ; Colak et al, ) or artichoke leaves (Abdel‐Kader et al, ) in rats with hepatotoxicity induced by carbon tetrachloride (CCl4) decreased MDA and diene conjugate (DC) levels and improved antioxidant parameters (i.e., activity of SOD, GPx, GSHm and CAT) and histopathological findings of hepatocytes compared with CCL4 treated rats. The artichoke leaf extract consumption in rats with paracetamol‐induced hepatotoxicity (El Morsy & Kamel, ), and in mice with acute alcohol‐induced liver injury (Tang et al, ) showed similar results favor to protect liver from toxicity induced by paracetamol and alcohol. But, Mehmetcik et al () observed that MDA and DC levels decreased and GPx activity and GSH level increased, whereas SOD activity and levels of vitamin E and vitamin C did not change significantly in liver tissue of rats with carbon tetrachloride‐induced hepatic injury after administration of artichoke leaf extract (1.5 mg/kg) for 2 weeks.…”
Section: Resultsmentioning
confidence: 91%
“…The antioxidant agents in Citrullus lanatus may be the reason it has a dose-dependent hepatotherapeutic function, hence, increasing the dose of Citrullus lanatus rind treatment may probably increase its therapeutic manifestations in relation to liver function. The ALT, ALP, AST [19], Total protein, Albumin, Total Bilirubin are the most sensitive biochemical markers employed in the diagnosis of hepatic dysfunction [20].Treatment with moderate and high doses of citrullus lanatus rind methanolic extract resulted in significant reduction in serum levels of ALT, ALP and AST. Low dose treatment of the extract caused no significant change in serum ALT, ALP and AST in comparison with the control.The findings of this study is in agreement with earlier reports [3,21].…”
Section: Discussionmentioning
confidence: 99%
“…Activities of serum Aspartate transaminase (AST) and Alanine transaminase (ALT) were assayed by the reitman and frankel calorimetric method [19] in which 0.2 ml of serum reacted with 1ml of substrate (Aspartate and α-ketoglutarate for AST, while alanine and α-ketoglutarate for ALT, in phosphate buffer pH 7.4) and was incubated for an hour in the case of AST and 30 minutes for ALT.…”
Section: Test For Alanine Transaminase (Alt) and Aspartate Transaminamentioning
confidence: 99%
See 1 more Smart Citation
“…Alcoholic liver damage caused by excessive drinking accounts for an important proportion in liver diseases and the incidence and mortality of ALD have been increased in recent years (Koneru et al, 2017;Tang, et al, 2017). The course of ALD usually manifests as fatty liver at the beginning and turns into alcoholic hepatitis, alcoholic liver fibrosis, and alcoholic cirrhosis.…”
Section: Introductionmentioning
confidence: 99%